OPTIMASI PRODUKSI HIJAB DENGAN FUZZY LINEAR PROGRAMMING - Martini Martini (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
o meet the needs of the wearer veil or hijab, then many models of hijab are easy to use and look good. Many manufacturers and home-industry that produce hijab with various models and affordable prices. Models are also tailored to the age of the wearer or a universal means it can be used by all people from teenagers to adults. In producing hijab cannot be separated from the observation of the manufacturer of the model of the most desirable. One of the problems facing the hijab producers is how many hijabs will be made with all the constraints. Seeing from the many uses of hijab by Muslim-women then the production of hijab was adjusted to the needs of course with a relatively cheap price and good quality. From the above problems, the author solves this problem of hijab production using Fuzzy Linear Programming to determine the right amount for each model and with maximum profit. The Simplex Method is used to calculate in determining the basic variable and its purpose function.